Annotated record of the detailed examination of Mn deposits in the Atlantic Ocean - Ericson, David B; Wollin, Goesta (Supplement to: Ericson, DB; Wollin, G (1973): Precipitation of manganese oxide in deep-sea sediments. In: Phase I Report - Inter-University Program of Research on Ferromanganese Deposits of the Ocean Floor. Seabed Assessment Program, IDOE, NSF, Washington D.C., USA, 99-103, hdl:2027/wu.89033915380, 1973)
In addition to the large nodules of manganese dioxide that pave some regions of the ocean floor, much finely divided (<1 mm) manganese dioxide occurs within the sediment column. The fine material is a good deal more widely distributed than the large nodules, but because of the almost microscopic size of the finely divided manganese oxide, it is easily overlooked. However, the micronodules and specks of manganese oxide on the tests of forarainifera are conspicuous when the washed course fractions (>74 micron) of sediment samples prepared for the study of foraminifera are examined with a microscope. As a byproduct of our study of the foraminifera in many deep-sea sediment cores, thousands of washed samples have accumulated in our laboratory together with notes on the occurrence of manganese oxide in cores. The objective of our study has been to search for clues regarding the conditions most favorable for precipitation of manganese oxide, by reviewing our notes and re-examining some of the washed samples, and particularly to look for a possible connection between vertical variations in abundance of manganese oxide and the climatically induced layering of the cored sediments.